A new shallow water species of the palaemonid shrimp genus Palaemon Weber, 1795 (Decapoda: Caridea) from Japan - Komai, Tomoyuki; Hanai, Motoya (Zootaxa, 2024)
During a survey of the shallow water decapod fauna in the Miura Peninsula, Kanagawa Prefecture, central Japan, four specimens of a new palaemonid shrimp, Palaemon parvibrachium n. sp., were collected from sea grass beds of Nanozostera japonica (Ascherson & Graebner) Tomlinson & Posluszny, 2001. The new species appears morphologically similar to P. serrifer (Stimpson, 1860), one of the most common representatives of Palaemon Weber, 1795 in Japanese waters, but the short carpus of the second pereopod and the different live colouration readily differentiate the new species from the latter. A DNA barcode (a partial fragment of the mitochondrial CO1 gene), as well as a partial fragment of the mitochondrial 16S rRNA gene, are provided to genetically characterize the new species.